Evaluation of the Immune System State in Patients with Chemoresistant Pulmonary Tuberculosis Depending on the Clinical Form - O.M. Raznatovskaya (Zaslavsky O.Yu., 2013)
The objective of the work was to assess the state of the immune system in patients with chemoresistant pulmonary tuberculosis, depending on the clinical form in terms of cytokines, leukocyte counts and haematological indices. Assessment of the state of immunity was performed at the beginning of treatment in 60 patients with chemoresistant pulmonary tuberculosis. Studying levels of interleukin-2, -6, -4, -10 and tumor necrosis factor alpha (TNF-α) in blood serum has been carried out by enzyme-linked immunosorbent assay. All patients with chemoresistant pulmonary tuberculosis we determined progression of activity of a specific process with a significant prevalence of humoral immunity and maximum inhibition of the cellular immunity, the predominance of early cytokine production - TNF-α.